Spectral analysis for tilted fiber Bragg gratings in the corrosion detection for concrete structure - Kwong, Kok Zee; Udos, Waldo; Lim, Kok-sing; Lee, Foo Wei; Tan, Chee Ghuan; Samion, Muhamad Zharif; Ahmad, Harith (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
An effective corrosion monitoring technique is sought after by the engineers for assessing the steel bar corrosion at the early stage for the maintenance and repair works, especially in the corrosive environments, such as coastal and marine. In this work, tilted fiber Bragg grating (TFBG) with the optical sensor is employed in corrosion monitoring of a reinforced concrete structure. Taking advantage of the high sensitivity of TFBG cladding resonance wavelengths to the change in the surrounding medium, the sensor is mounted on the steel bar that is embedded in a concreted block during an accelerated corrosion process. The acquired transmission spectrum of the TFBG during the procedure is digitally processed using Fourier Transform to produce an index that is sensitive to the generated corrosion product surrounding the TFBG sensor. This eases the analysis of the sophisticated TFBG transmission spectra. The generated index can be used as an indicator (indicator J) for the corrosion process of the embedded steel bar in the concrete structure. This indicator J can act as an indicator to describe the corrosion activity and corrosion level at a specific point of the steel bar in concrete structures.
Optica Applicata, Vol. 52, 2022, nr 3, s. 429-439
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; tilted fiber Bragg grating; optical spectral analysis; Fourier transform; corrosion; steel bar